Air pollution and life expectancy: the role of education and health expenditure in China - Yezhi Zhang; Manshu Huang; Yanshou Zhang; Xuan Kong; Kunpeng Shi; Bingcheng Zhu (Frontiers in Public Health)
Health is directly linked to SDG 3, “Good Health and Well-being,” which aims to ensure healthy lives and promote well-being for all ages. Achieving this goal involves improving health outcomes, including increasing life expectancy (LEX) and reducing mortality rates. Therefore, the current study aims to examine the impact of Air pollution’s on LEX, and the role of education, and health expenditure in achieving the SDG 3 in China from 2000 to 2023. This study utilizes the Auto Regressive distributed lag (ARDL) model. We use the Fully modified ordinary least squares (FMOLS) and Dynamic ordinary least squares (FMOLS) methods for robustness analysis. The results show that CO2 emissions and inflation negatively impact LEX, while education, health expenditure, and GDP positively affect LEX. Policymakers should prioritize reducing CO2 emissions through stricter environmental regulations to improve public health. Increased investment in education and healthcare, alongside policies that boost GDP growth, should be emphasized to enhance life expectancy further. Additionally, controlling inflation through sound economic policies will mitigate its negative impact on life expectancy.